From Smart to Wise : Acting and Leading with Wisdom - Kaipa, Prasad, 1955- and Radjou, Navi (India Random House India, 2013)
Drawing on stories of historical wise leaders such as Bill Gates, and Warren Buffet, the authors identify six characteristics of wise leaders and offer a framework to help readers develop their own style of wise leadership. They offer an approach that balances the two styles to achieve a form of wise leadership that is both functional and smart.
Keywords: Leadership -- Wisdom